Downs syndrome and its screening: how aware are we? - Nambiar, Murli Krishna; S., Roopa P.; C., Nisha; Kumar, Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Down syndrome (DS) is the most common chromosomal abnormality found in live-born babies. The objectives of this study were to assess the knowledge, attitude and practices of pregnant women regarding Down syndrome and its screening. Methods: This was a prospective study done in the Department of Obstetrics and Gynecology, in a tertiary care hospital. All pregnant ladies who attended the antenatal clinic and consented for the study were included. A prevalidated questionnaire was given to these women and data was collected. Responses to pregnant women’s knowledge, attitudes and practices were evaluated in a three-point scale of yes/no/ don’t know. All correct answers or all but one correct answer was scored good and the percentage was calculated. Results: A total of 267 pregnant women were included in the study. Of the 267 women only 156 (58.4%) had heard about Down syndrome. Eighty five percent of the women unanimously agreed that Down syndrome babies had mental impairment. But only 21.1% patients had good knowledge score on Down syndrome. Eleven percent had good knowledge regarding Down syndrome screening tests. Almost sixty five percent of the women had the right attitude towards screening tests and 46.1% patients had followed good practice. Conclusions: Informed decision making rather than imposed decision making must be practiced. Compulsory and effective education regarding Down syndrome and its screening must be provided to all patients at the earliest antenatal visit. The gap between women’s knowledge, theirs attitudes and practice has to be addressed to. Non-invasive prenatal testing might be the future and is quickly bring about a shift in the paradigm in prenatal screening.